The sociocultural basis of Indonesian philanthropy: Keeping citizens willing to share amid a pandemic - Iqbal Arpannudin; Karim Suryadi; Elly Malihah; Leni Anggraeni (Universitas Negeri Yogyakarta, 2021)
This article aims to dig deeper into the concept of Indonesian philanthropy in dealing with the pandemic seen from the social base of the Indonesian people. This study uses a qualitative approach with the grounded theory method. This research results show a collective awareness of Durkheim's understanding that characterizes mechanical solidarity; in the case of philanthropy in Indonesia, it is at the intersection of mechanical and organic solidarity. The strengthening of generosity can be explained from the theory of social facts that there are non-material social facts that shape the spirit of the Indonesian people's philanthropic movement, namely generosity and collective awareness that characterize mechanical solidarity in rural areas that occurs in modern society with organic solidarity.